A New Iteration Process for Approximate Common Fixed Points for Three Non-Expansive Mapping - Sabri , Raghad I. (Iraqi Journal of Science, 2025)
A point that stays unchanged during a transformation is known as a fixed point(Fp). Such points play an important part in several mathematical domains. Applying Fp theory approaches allows for the efficient derivation of suitable solutions for operator equations that describe phenomena in several nonlinear scientific disciplines. The goal of solving these equations is to identify the Fp and its approximation. In this paper, a new iteration process is provided to approximate common fixed points (CFp) for non-expansive mapping (Non-exp map). Some convergence theorems have been established and the results obtained are confirmed with examples and tables. A numerical example is given to demonstrate that a novel process converges more rapidly than other existing iteration procedures.